Poly(butylene succinate‐co‐butylene adipate)/polyethylene oxide blends for controlled release materials: A morphological study. Issue 3 (9th September 2015) - Cottaz, Amandine; Khalil, Fadi; Galland, Sophie; Jbilou, Fouzia; Adt, Isabelle; Degraeve, Pascal; Joly, Catherine
ABSTRACT Varying the formulation and processing conditions of polymer blends allows the design of materials with a large range of morphologies. Active materials embedding active compounds in a devoted phase are promising applications of such blends, offering possible various transport properties. In this study, 13 poly(butylene succinate‐co‐butylene adipate) (PBSA)/polyethylene oxide (PEO) blends were extruded in a slit die. Their morphologies were characterized by water extraction (selective PEO dissolution), FTIR spectroscopy, and differential scanning calorimetry. Transport properties were assessed by water vapor permeation and fluorescein release as model migrant. Indeed, the desorption in water of fluorescein (previously entrapped in PEO) was monitored to preliminary investigate the release properties of these materials: two morphologies were obtained (i) pseudo multilayer films made of PEO‐rich layer/PBSA‐rich layer/PEO‐rich layer and (ii) PEO nodules dispersed in the PBSA‐rich matrix for the highest PBSA contents. The first systems were erodible ones with an uncontrolled fast delivery by PEO dissolution whereas the second ones showed a controlled release by permeation through the PBSA matrix from PEO nodules. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42874.